PID Temperature Control on Blood Warmer Equipped with Patient Temperature and Blood Temperature - Clarissa Grace Santoso; Torib Hamzah; Syaifudin Syaifudin; Muhammad Umer Farooq Mujahid (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Body temperature in humans varies greatly depending on the location where the reading is taken. Normal core body temperature in humans is maintained by the hypothalamus and usually ranges from 36.5°C to 37.5°C. One of the causes of failure in the blood transfusion process can cause death in humans, one of the factors is the blood temperature that is too high or too low during the blood transfusion process can cause the blood to become frozen or damaged, therefore the purpose of this tool is to lower the blood temperature admission to the patient can be achieved so that there is no reduction in temperature or decrease in temperature and so that the blood is not allowed to get too hot because it can cause damage to red blood cells. This study uses the DS18B20 Sensor to control the heater with PID and Fuzzy controls, the MLX90614 Sensor to set the temperature according to the patient's body temperature and the Optocoupler Sensor as an indicator when fluids run out. When using the PID control with Kp = 4, Ki = 1, and Kd = 4, a faster response time is obtained and there is an overshoot with the highest error value of 0.77 and an average error value of 0.02. The results of the study are displayed on the TFT Nextion. From the results of the research above, it can be concluded that using PID control the response time is faster, but there are drawbacks to high overshoot.